Application of lanthanum-silicon apatite loaded nickel-based catalyst in hydrogen production from acetic acid
The nickel-based catalyst supported by lanthanum silicon apatite was prepared by co-precipitation method to form a Ni-La-Si-O active center, which solved the problem of the catalyst being prone to carbon accumulation and sintering in the acetic acid autothermal reforming reaction, and achieved efficient acetic acid conversion and stability of hydrogen yield.
Patent Information
- Application Number
- CN202510060835.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-08
AI Technical Summary
The existing catalysts tend to accumulate carbon and sinter in the acetic acid autothermal reforming reaction, which has poor stability and leads to the deactivation of the catalyst.
The nickel-based catalyst supported by lanthanum silicon apatite was prepared by co-precipitation method to form a Ni-La-Si-O active center, which improves the catalyst's resistance to carbon deposits, thermal stability and sintering resistance.
In the acetic acid autothermal reforming reaction, the acetic acid conversion rate of the catalyst is close to 99%, and the hydrogen yield is stable, which effectively inhibits the generation of by-products and maintains the stable activity of the catalyst.
Smart Images

Figure CN119771427A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lanthanum-silicon-apatite-loaded nickel-based catalyst for producing hydrogen through autothermal reforming of acetic acid, and belongs to the field of producing hydrogen through autothermal reforming of acetic acid. Background Art
[0002] Compared with hydrogen production from fossil raw materials, hydrogen production from biomass and its derivatives is a hydrogen production route with good development prospects. Biomass has a wide range of sources and can be obtained from agriculture, forestry and urban waste; biomass oil obtained by thermal cracking of biomass contains hundreds of compounds, among which acetic acid (HAc) is the main component of its aqueous phase, with a content of up to 33wt%, which is a cheap and readily available renewable reforming hydrogen production raw material.
[0003] Generally speaking, the acetic acid reforming process used for hydrogen production can be divided into three categories: steam reforming, partial oxidation reforming and autothermal reforming. Among them, the acetic acid steam reforming process is a strong endothermic reaction with high heat exchange requirements; only oxygen or air is introduced into the partial oxidation reforming reaction, and the hydrogen yield is low; in the acetic acid autothermal reforming process, oxygen and water vapor are introduced into the feed at the same time, and the heat balance of the entire reaction system is achieved by adjusting the molar ratio of oxygen to reactants.
[0004] Efficient and structurally stable reforming catalysts play a vital role in the adsorption and activation of reactant molecules, the breaking of CC and CH bonds in acetic acid molecules and the formation of new bonds, regulating the transformation pathway of intermediate products, inhibiting the formation of by-products, and promoting the production of hydrogen. As a non-precious metal catalyst, Ni-based catalysts can effectively activate CC, CH, CO and OH bonds in acetic acid molecules during the process of acetic acid autothermal reforming to produce hydrogen, promote acetic acid conversion and hydrogen production, and therefore have received extensive attention in acetic acid autothermal reforming. However, in Ni 0 At the active site, acetic acid removes OH to form intermediates such as CH3CO*, which further decompose to form CH3* species. The accumulation of its dehydrogenation product C* species leads to carbon deposition, which in turn deactivates the catalyst. At the same time, in an oxidizing atmosphere, the rapid increase in the reactor bed temperature leads to the aggregation of active components, forming large-size Ni particles, which reduce the activity for acetic acid conversion and cause the catalyst activity to decrease.
[0005] Aiming at the sintering and carbon deposition problems of catalysts in the autothermal reforming conversion process of acetic acid, the present invention prepares a lanthanum-silicon-apatite-supported nickel-based catalyst by a coprecipitation method, forms a Ni-La-Si-O active center, and is used in the autothermal reforming hydrogen production process of acetic acid.
[0006] On the one hand, in order to solve the problem of directional conversion of acetic acid, water and oxygen in the process of acetic acid autothermal reforming, the La 10(SiO4)6O3 apatite structure, whose space group is P63 / m, has remarkable oxygen ion conductivity and structural stability; in this structure, [SiO4] 4- The tetrahedrons are quasi-densely packed to form a three-dimensional (3D) framework structure of the crystal. The free oxygen O(Ⅳ) is located in the oxygen channel formed by the framework, at the center of the two equilateral triangles composed of La cations (La1 is located at the 4f position and La2 is located at the 6h position). The excess oxygen is located at the edge of the free oxygen O(Ⅳ) oxygen channel, that is, the gap between La, Si and O(Ⅲ), which is called interstitial oxygen O(V) because it does not belong to any [SiO4] 4- The tetrahedron, so O(Ⅳ) and O(Ⅴ) are easy to move in the oxygen channel, and the cation vacancy causes local charge imbalance in the lattice, resulting in the weakening of the Coulomb force between the oxygen ion at the 2a position and the surrounding La, which reduces the binding force of La at the 6h position on the oxygen at the 2a position, thereby improving the mobility of oxygen in the channel, thereby ensuring that the CH3CO* intermediate formed by the de-OH* of the CH3COOH molecule can be effectively oxidized to generate carbon-containing products such as CO and CO2, avoiding the carbon deposition precursor covering the active site Ni 0 , resulting in catalyst deactivation.
[0007] On the other hand, in the lanthanum silicate-type crystal constructed by the present invention, [SiO4] 4- The tetrahedrons form a network structure by sharing the top, and the presence of non-bridging oxygen means that each oxygen atom can be shared by at most two tetrahedrons. This connection method enhances the three-dimensional network structure of the crystal, thereby improving its thermal stability. The Si-O bond is one of the stable chemical bonds in silicate compounds, with a bond length between 0.161 and 0.164 nm and a high bond force constant, which makes the Si-O bond remain stable at high temperatures. The high thermal stability of this structure provides a stable reaction interface for the adsorption and activation of CH3COOH.
[0008] In addition, the rare earth element La has a special 4f electronic configuration on the Ni-La-Si-O active center formed by the catalyst. It provides electrons as a Lewis base and adjusts the number and strength of the Lewis basicity formed by interacting with the Lewis acid center, thereby promoting the adsorption and activation of the acidic reactant molecule CH3COOH and driving the Boudouard reaction in reverse (CO2+C→2CO), reducing catalyst carbon deposition; at the same time, La doping causes the lattice to be stretched, destroying the original crystal symmetry and order, thereby causing lattice distortion, which further leads to the displacement of the d-band center; according to the d-band theory, the position of the d-band center plays a decisive role in the adsorption energy and reaction activation energy barriers. The stretched lattice strain causes the d-band center of the metal to move up, thereby enhancing the binding ability of the reaction intermediates and promoting the adsorption and activation of the metal Ni active center and oxygen-containing intermediates (CH3COO*, CH3CO*, CH2CO*, CO* and O*).
[0009] The catalyst of the present invention constructs a lanthanum silicon apatite-supported nickel-based catalyst through innovations in structure and composition, thereby improving the catalyst's carbon deposition resistance, thermal stability and sintering resistance in an acetic acid autothermal reforming reaction. Summary of the invention
[0010] The technical problem solved by the present invention is to provide a new catalyst which is resistant to carbon deposition, has high thermal stability and is resistant to sintering, in view of the problem that the existing catalyst is prone to carbon deposition and sintering and has poor stability in the autothermal reforming reaction of acetic acid, resulting in catalyst deactivation.
[0011] The present invention uses Ni as an active component, introduces La and Si components, and adopts a coprecipitation method to prepare a lanthanum silicon apatite-supported nickel-based catalyst to form a Ni-La-Si-O active center. The catalyst of the present invention is used in the autothermal reforming of acetic acid to produce hydrogen. Under the condition of a reaction temperature of 700°C, the conversion rate of acetic acid (HAc) is close to 99%, and the hydrogen yield is stable at about 2.70 mol-H2 / mol-HAc.
[0012] Technical solution of the present invention:
[0013] The present invention adopts a coprecipitation method to prepare a nickel-based catalyst supported by lanthanum silicate apatite in view of the characteristics of acetic acid autothermal reforming. The molar composition of the catalyst of the present invention is (NiO) a (LaO 1.5 ) b (SiO2) c , wherein a is 0.75-0.86, b is 1.61-1.82, and c is 0.75-1.31; the weight percentage composition calculated as oxides is: nickel oxide 14.0%-16.0%, lanthanum oxide 65.4%-74.1%, silicon dioxide 11.3%-19.8%, and the sum of the weight percentages of each component is 100%.
[0014] The specific preparation method steps are as follows:
[0015] 1) According to the molar composition of each component in the catalyst (NiO) a (LaO 1.5 ) b (SiO2) c , where a is 0.75-0.86, b is 1.61-1.82, and c is 0.75-1.31. Weigh appropriate amounts of nickel nitrate and lanthanum nitrate into a beaker, add deionized water and stir until dissolved, which is recorded as solution 1#; at the same time, weigh a certain amount of sodium silicate, add appropriate amount of deionized water and continue stirring until all dissolved, to obtain solution 2#;
[0016] 2) Prepare a mixed solution containing Na2CO3 and NaOH, denoted as solution 3, in which metal cations Ni, La and silicate SiO3 2- The molar ratio of the total charge number to the hydroxide is 1:8, and the molar ratio of the carbonate to the hydroxide is 1:16; at a water bath temperature of 65°C, solutions 1# and 2# are dripped into the beaker drop by drop, and solution #3 is dripped drop by drop during the process to control the pH of the mixed solution within the range of 11±0.5. After completion, the mixture is maintained at a constant temperature of 65°C for aging for 24 hours;
[0017] 3) After aging, the precipitate was collected by filtration and washed with deionized water three times, and the precipitate was placed in an oven at 105°C and dried for 12 hours to obtain a catalyst precursor;
[0018] 4) The dried precursor sample was placed in a tube furnace and heated to 900°C at a heating rate of 10°C / min. After calcination for 4 hours, it was reduced in a H2 atmosphere at a temperature of 600-800°C for 1 hour to form Ni-La-Si-O active centers. Its typical crystal structure is shown in the attached figure. Figure 1 As shown, a nickel-based catalyst supported by lanthanum silicate apatite is obtained, with Ni / La 10 (SiO4)6O3 structure, and at the same time, a mesoporous structure is constructed. Its typical BJH pore size distribution is shown in the attached figure. Figure 2 As shown; nitrogen is used as a carrier gas, and a mixed gas with a molar ratio of acetic acid / water / oxygen = 1 / (3.0-5.0) / (0.2-0.5) is introduced through the catalyst bed to carry out an acetic acid autothermal reforming reaction at a reaction temperature of 600-800°C.
[0019] Beneficial effects of the present invention:
[0020] 1) The catalyst of the present invention uses Ni as the active component, introduces La and Si components, and uses a coprecipitation method to prepare a nickel-based catalyst supported by lanthanum silicate apatite. The active component Ni is highly dispersed in La 10The (SiO4)6O3 apatite structure promotes the formation of Ni-La-Si-O active centers, effectively improving the activity of the catalyst and its ability to resist carbon deposition and sintering.
[0021] 2) ① La constructed by the catalyst of the present invention 10 (SiO4)6O3 apatite structure, whose space group is P63 / m, has significant oxygen ion conductivity; in this three-dimensional skeleton structure, free oxygen O(IV) and interstitial oxygen O(V) can move freely in the three-dimensional structure of the crystal, and La 10 The cation vacancy on the La1 site in the (SiO4)6O3 structure results in significant cation vacancies, which makes its composition closer to La 9.64 Si 5.77 O 26 These cation vacancies cause local charge imbalance in the lattice, thereby further improving the migration ability of oxygen ions to promote the CH3CO* intermediates formed by the de-OH* of CH3COOH molecules to be effectively oxidized to generate carbon-containing products such as CO and CO2, avoiding the carbon deposition precursor covering the active site Ni 0 , inhibiting catalyst deactivation; in addition, the constructed La 10 The positions of oxygen atoms in the (SiO4)6O3 apatite structure are disordered, which makes it easier to produce a large number of oxygen vacancies, thereby adsorbing and generating surface active *O2 molecules, thereby increasing the mobility of active oxygen species O*, effectively oxidizing carbon-containing intermediates such as *CHx and C*, and further improving the catalyst's ability to resist carbon deposition.
[0022] ② On the Ni-La-Si-O active center formed by this catalyst, the rare earth element La has a special 4f electronic configuration, which acts as a Lewis base to provide electrons and adjust the number and strength of Lewis basicity in the system by interacting with the Lewis acid center, thereby promoting the adsorption and activation of the acidic reactant molecule CH3COOH and driving the Boudouard reaction in reverse (CO2+C→2CO), reducing catalyst carbon deposition.
[0023] ③ Ni / La constructed by the present invention 10 In the (SiO4)6O3 structure, the lattice stretching caused by La doping destroys the symmetry and order of the crystal, resulting in lattice distortion. This distortion causes the d-band center of metallic Ni to shift upward, enhancing its adsorption and activation ability with oxygen-containing intermediates (such as CH3COO*, CH3CO*, CH2CO*, CO*, and O*), thereby improving the catalytic activity.
[0024] 3) The lanthanum silicate apatite supported nickel-based catalyst with a mesoporous structure prepared by the coprecipitation method of the present invention is reduced by hydrogen at 700°C to produce active metal Ni 0 Highly dispersed on the carrier to form Ni / La10 (SiO4)6O3 structure, with strong metal-support interaction, thus effectively inhibiting the sintering of nickel nanoparticles; the support La 10 The bond length of Si-O bond in (SiO4)6O3 structure is between 0.161 and 0.164nm, the bond force constant is relatively high, and it is still stable at high temperature. 4- The tetrahedrons are connected by sharing the top to form a network structure. This connection method improves its high thermal stability. The high thermal stability of this structure can provide a stable reaction interface for the reaction, while promoting the adsorption and activation of reactants CH3COOH, H2O, and O2 into target products such as H2 and CO2, while maintaining the dispersion of active nickel to further improve the catalyst's ability to resist carbon deposition.
[0025] 4) The results of the acetic acid autothermal reforming reaction show that the catalyst of the present invention can induce the efficient conversion of the reactant acetic acid molecules during the acetic acid conversion process, effectively inhibit the production of by-products such as methane and acetone, improve hydrogen selectivity, and has the characteristics of anti-coking, stable activity, and sintering resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 : X-ray diffraction spectrum of the catalyst after reduction treatment of the present invention;
[0027] Figure 2 : BJH pore size distribution diagram of the catalyst of the present invention;
[0028] Figure 3 : X-ray diffraction spectrum of the catalyst of the present invention after reaction. DETAILED DESCRIPTION
[0029] Reference example one
[0030] Weigh 0.866g of Ni(NO3)2·6H2O, add 30mL of deionized water and dissolve it in a beaker; weigh 2.000g of γ-A12O3 and pour it into a beaker for impregnation; place it at room temperature for 12h, dry it, and calcine it at 700℃ in a tube furnace for 4h to obtain a CDUT-NA catalyst, forming a Ni-based catalyst supported on γ-A12O3; the weight percentage composition of the catalyst in terms of oxides is: nickel oxide (NiO) is 10.0%, and γ-A12O3 is 90.0%.
[0031] The activity evaluation of acetic acid autothermal reforming reaction is carried out in a continuous flow fixed bed reactor. The catalyst is ground and tableted, then sieved into 20-40 mesh particles, and 0.1-0.2g is weighed and loaded into the reactor, and reduced in H2 at a temperature of 700°C for 1h; then the acetic acid-water mixed solution is injected into the vaporizer by a constant flow pump for vaporization, and then mixed with nitrogen, and nitrogen is used as the internal standard gas to form a reaction raw gas with a molar ratio of CH3COOH / H2O / O2 / N2=1 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5), and this raw gas is passed into the reaction bed. The reaction conditions are 600-800°C, normal pressure, and a space velocity of 15000-50000mL / (g-catalyst·h), and the reaction tail gas is analyzed online by a gas chromatograph.
[0032] The catalyst CDUT-NA was tested for its activity in acetic acid autothermal reforming. When the reaction conditions were normal pressure, space velocity 25000mL / (g-catalyst·h), reaction temperature 700℃, and raw gas acetic acid / water / oxygen = 1 / 4.0 / 0.28, the initial conversion rate of acetic acid was 97.5%, the initial yield of hydrogen was 2.50 mol-H2 / mol-HAc, the selectivity of CO2 was about 48.9%, the selectivity of CO was about 25.0%, and the selectivity of CH4 was 0.3%; as the reaction proceeded, the reaction activity of the catalyst gradually decreased. After 10 hours of acetic acid autothermal reforming reaction, the yield of hydrogen decreased to 2.3 mol-H2 / mol-HAc, the selectivity of CO2 decreased to about 47.0%, the selectivity of CO decreased to about 22.0%, the selectivity of by-product CH4 also increased to about 0.4%, and the by-product acetone was about 0.1%. Characterization results such as XRD and BET show that the catalyst has poor stability during the autothermal reforming of acetic acid, and sintering, carbon deposition and partial oxidation occur, resulting in low activity.
[0033] Embodiment 1
[0034] Weigh 4.671g of Ni(NO3)2·6H2O and 14.800g of La(NO3)3·6H2O, add 30mL of deionized water and stir until dissolved, record as solution 1#; weigh 2.503g of Na2SiO3, add 30mL of deionized water, stir evenly to obtain solution 2#; weigh 13.584g of NaOH and 2.250g of Na2CO3, add 30mL of deionized water to prepare solution 3#; then, at 65℃, drip solutions 1# and 2# into a beaker drop by drop, and at the same time drip Solution 3# was added to control pH = 11 ± 0.5, and the temperature was maintained for aging for 24 hours; after the aging, the precipitate was collected by filtration and washed with deionized water for 3 times, and the precipitate was transferred to a 105°C oven for drying for 12 hours to obtain a catalyst precursor; the sample was placed in a tubular furnace, heated to 900°C at a heating rate of 10°C / min, and calcined at this temperature for 4 hours, and then reduced at 700°C in a H2 atmosphere for 1 hour to obtain a lanthanum silicon apatite-supported nickel-based catalyst, forming a Ni / La with Ni-La-Si-O active center. 10 (SiO4)6O3 structure, i.e., the catalyst CDUT-NLS of the present invention, its typical crystal structure is shown in the attached Figure 1 The results of nitrogen low temperature physical adsorption and desorption test show that the average pore size of the catalyst is 12.5 nm, and its typical mesoporous structure is as shown in the attached Figure 2 As shown; the molar composition of the catalyst is (NiO) 0.79 (LaO 1.5 ) 1.68 (SiO2) 1.01 The weight percentage composition of the oxides is: 15.0% nickel oxide, 69.6% lanthanum oxide, and 15.4% silicon dioxide.
[0035] The activity of the CDUT-NLS catalyst was investigated by the autothermal reforming reaction of acetic acid. Under the reaction conditions of space velocity of 25000 mL / (g-catalyst·h), reaction temperature of 700℃, and feed molar ratio of CH3COOH / H2O / O2=1 / 4.0 / 0.28, the conversion rate of acetic acid by the catalyst was stable at 99%, the H2 yield was stable at about 2.70 mol-H2 / mol-HAc, the CO2 selectivity was about 66.0%, and the CO selectivity was maintained at about 33.7%. No byproducts of methane and acetone were detected, and the catalyst activity remained stable without deactivation. The results of low-temperature nitrogen physical adsorption and desorption showed that the specific surface area of the catalyst was 12.5m 2 / g, pore volume is 0.081cm 3 / g, and an average pore size of 12.5nm, which is a mesoporous material. XRD and other characterization results show that the catalyst has no obvious carbon deposition and no sintering after the autothermal reforming reaction. Figure 3As shown, the catalyst has a high and stable conversion rate for acetic acid, can effectively inhibit the production of by-products such as methane and acetone, and has high activity for hydrogen production from acetic acid autothermal reforming.
Claims
1. Application of lanthanum silicon apatite supported nickel-based catalyst in the process of hydrogen production by autothermal reforming of acetic acid, characterized in that: The catalyst is reduced in a H2 atmosphere at 600-800°C for 1h, and nitrogen is used as a carrier gas. A mixed gas with a molar ratio of CH3COOH / H2O / O2=1 / (3.0-5.0) / (0.2-0.5) is introduced through the catalyst bed to react at a reaction temperature of 600°C-800°C. The catalyst is prepared by the following method: according to the catalyst composition, a certain amount of nickel nitrate and lanthanum nitrate are weighed, and an appropriate amount of deionized water is added and continuously stirred until dissolved, which is recorded as solution 1#; at the same time, a certain amount of sodium silicate is weighed, and an appropriate amount of deionized water is added and continuously stirred until completely dissolved, which is recorded as solution 2#; a mixed solution containing Na2CO3 and NaOH is prepared, which is recorded as solution 3#, wherein the metal cations Ni, La and the silicate SiO3 2- The molar ratio of the total charge number to the hydroxide is 1:8, and the molar ratio of the carbonate to the hydroxide is 1:16; while maintaining a water bath temperature of 65°C, solutions 1# and 2# are dripped into a beaker drop by drop, and solution #3 is dripped at the same time to control the pH of the mixed solution within the range of 11±0.5, and the mixture is aged at 65°C for 24 hours; after the aging, the precipitate is collected by filtration and washed with deionized water for 3 times, and the precipitate is placed in an oven at 105°C and dried for 12 hours, and then heated to 900°C at a heating rate of 10°C / min in a tubular furnace, calcined for 4 hours, and then reduced in a H2 atmosphere at a temperature of 600-800°C for 1 hour to form a Ni / La 10 A nickel-based catalyst supported by lanthanum silicate with a (SiO4)6O3 structure; the molar composition of the catalyst in terms of oxide is (NiO) a (LaO 1.5 ) b (SiO2) c , wherein a is 0.75-0.86, b is 1.61-1.82, and c is 0.75-1.31; the weight percentage composition calculated as oxides is: nickel oxide 14.0%-16.0%, lanthanum oxide 65.4%-74.1%, silicon dioxide 11.3%-19.8%, and the sum of the weight percentages of each component is 100%.
2. The use of the lanthanum silicon apatite supported nickel-based catalyst in the process of producing hydrogen from acetic acid autothermal reforming according to claim 1, characterized in that: The catalyst is composed of 15.0% nickel oxide, 69.6% lanthanum oxide and 15.4% silicon dioxide in terms of oxide weight percentage.